Emprego de geotecnologias na gestão de unidades de produção avícola - Sangoi, Luiz Fernando (2005)
Considering the social and economic importance of poultry production, and also with the objective of demonstrating the applicability of peomatic techniques in the management of poultry integrations: georeferencing, storing, monitoring, analysing, and managing information and data collected by Enterprises. The objective of this dissertation was the use of geoprocessing tools to establish a higher speed to the decisions of bio safeting and safety. The utilization of the combined and comparative management, improving the performance and the economic viability of the poultry integrations. In the study proposed we used these geotechnologies at Avipal S.A., which works with the internal and external market in the segment of poultry farm production. It has been in thirty five cities in the Taquari Valley of Rio Grande do Sul State, having 1.207 producers integrated with 1.525 aviaries with a lodging capacity for 22.844.524 birds. The case studied, concerning the use of geotechnologies in the management of the integration of poultry farm at Avipal S.A. constituted basicaly of the mechanisms of technical capacity in the procedures of field position to the technicians of the poultry integrations; punctual georeferencing of the integration of poultry farm, identifying the entrance sign of the property, the headquarters of the property, the front and rears of the aviaries and composturas ; the creation of a data bank of the integrated products and the utilization of modules of spacing and visualization of the data base georeferentiated in the managing system and rural territorial in formation as well, which made the geographic research location possible, reports of the efficiency indexes and sanitary occurrences, research of space location of integrated upon a digital base and in CAD drawing environment. This study made it possible to simulate situations of managing analyses and decision making in cases of bio safeting, such as the creation of a sanitary cord, if it were necessary, even discovering that the georeferencing and the spaciousness of properties, associated with the managing of them, allows the poultry farm enterprises the production of instant qualitative and quantitative information, generating fast and correct decisions, and besides execute in practice the legislation of the National Plan Of Poultry Farm Hygiene (PNSA), which is so important in the whole protection of the national poultry farm population.